Triplet state energy transfer in several proteins. - Grainger, D A (1977)
Energy transfer between excited triplet states of aromatic amino acid residues was observed at 1.4 degrees K. The distance necessary for energy transfer between monomeric tyrosine and tryptophan residues was determined to be roughly 63 A. Total phosphorescence decay rate constants for several proteins were determined while emission corresponding to tyrosine and tryptophan residues was monitored. The observed decay rate constants are interpreted in terms of intramolecular interactions of the polypeptide residues.